How are you peeling foods with moods - Freymann, Saxton; Elffers, Joost (New York Scholastic Inc., 1999)
Brief text and photographs of carvings made from vegetables introduce the world of emotions by presenting leading questions such as "Are you feeling angry"
Keywords: Vegetable carving; Emotions